PENGGUNAAN MERK NILON YANG BERBEDA PADA LALANGIT (Horizontal gillnet) TERHADAP HASIL TANGKAPAN IKAN BETOK (Anabas testudineus) - Siti Aminah (Faculty of Fisheries and Marine Resources of Lambung Mangkurat University-South Kalimantan, 2019)
The purpose of this research is to know (1) the description of the commonly used lalangit, (2) the amount of the catch (catch) are obtained from the difference insome brands of nylon that is used, (3) brands of nylon materials as the best lalangit (horizontal gillnet). The research method used was Random Design Group (RAK) with 6 treatments IE 6 types of different brands of nylon. Of research results obtained the most number of catches a lot on Lalangit using the brand damyl earn 50 catches the tail with a total weight of 1.728 gram, because in terms of construction or its material soft materials that cause the catch is not easy to escape from nets due to elastisitasan and the blue color of nylon can resemble aquatic conditions so that thegullible fish State of the waters and the obtained results the optimal catch.